Structural Optimization of Composite from Wind Turbine Blades with Horizontal Axis Using Finite Element Analysis. (2016) - Domnica, Stanciu Mariana; Ioan, Curtu; Ionut, Tesula
Abstract: Materials used in the development and construction of the blades are essential for the proper functioning of wind turbines. The challenges of engineers are related to the optimum combination of the following structural properties: optimum rigidity - specific gravity; lifetime to fatigue and flexibility; low cost of materials and processing to achieve the desired aerodynamic shape. The purpose of this paper is identification of risk areas of wind turbine blades and composite structural optimization of their structure in areas exposed to combined loading, using finite element analysis. Optimizing structural composites depending on risk areas is a difficult issue because it must take into account the aerodynamic profile, proper positioning of the center of gravity and dynamic and elastic center of blade so that during operation, will not develop the inertial masses to affect the functioning and integrity of the blades. In the first stage of the research, the blade structure with a length of 1.5 m and profile NACA 2412 was modeled from composite fiber reinforced polymer, with 7, 9, 11, 13, 15 layers of fiber glass fabric and mat with epoxy resin as matrix. Once static analysis, the risk areas where determined taking into account the maximum values of normal and tangential stresses. In the next stage, structural optimization and verification was performed, the state of stress and strain being compared to stress obtained initially. There were also determined the optimum package of composite taking into account the reduction of blade mass. It was found that increasing the number of layers in risk areas and their reduction to the blade tip leads to increasing resistance to static and dynamic loads. Orientation of layers can improve the static and dynamic behavior. The study aims to applying the finite element method in designing composites used in wind turbine blades structure, reducing the cost of production and improving the structure.